CHARACTER BUILDING IMPLEMENTATION MODEL: A REVIEW ON ADAB AKHLAK LEARNING - Muhammad Muhammad (Universitas Islam Negeri (UIN) Mataram, 2020)
The implementation of the 2013 curriculum for strengthening character building has many obstacles. Teacher’s understanding, limited resources, and mass media negative impact are identified as the hindrance of the implementation. The article aims to explore character building based on Adab Akhlak learning. For this purpose, the research uses the qualitative approach based on a literature review. The research data was obtained from research result which has been published (secondary research). The data findings were compiled, decoded, categorized, illustrated in a matrix, and then drawn conclusion and verification. The research result shows that it did not achieve character-building maximally because, first, it was lack of adequate follow-up after assessment/evaluation result; second, the cognitive aspect was always dominant in determining student’s achievement and learning completion. The values of attitude and behavior were not regarded as an authoritative reference to determine a student’s learning completion. The orientation of attitude and behavior assessment become student’s report “ornament”, however, it had not been accompanied by adequate followed-up, for instance, in the form of reward which can encourage on the developing and maintaining character values owned, and punishment which provide a deterrent effect and eliminate the possibility to repeat the violation. The success of character building in MA Plus Abu Hurairah Mataram lies on the courage to determine punishment policy for the offenders and consistent with the rules. The attitude and behavior become the standard measurement in assessing learning completion, it had 50% percentage in determining graduation.